PRACTICE OF EVALUATION OF SOCIAL JUSTIFIABILITY OF INVESTMENT PROJECTS IN THE EU - Popović, Goran; Coprka, Miodrag (Economics of Agriculture, 2011)
Valuation of investments and investment projects is a very important social activity. However, by the development of productive forces, accompanied by an accelerated exploitation of natural resources, and by growing of social expectations in the modern communities, investment decision-making includes also alternative economic opportunities. In such circumstances, the choice of the project is considered to be rational and justifiable only if it is better than others even in these non-economic areas. Therefore, consideration of investment projects in terms of their future impact on the wider social community is more and more important. Investments affect economic growth and social well-being, but in modern circumstances their role is significantly changed, especially in terms of sustainability. Therefore the EU increasingly encourages the corporate social responsibility in long-term strategies and plans of the companies, as well as the use of the methodology for evaluation of the social justifiability of investment projects. Also, there are other methodologies for evaluation of the social justifiability of investment projects, as it is the case with the methodology of the UN, which confirms that this area is extremely important in global relations.